Literature Review: Efektivitas Electronic Word of Mouth (e-Wom) dalam Mempengaruhi Minat Beli Produk - Citra Wijaya, Katterina Pangestu; Aulia, Virda; Haq, Sofia; Fahira, Faisyah; Kusanadi, Syalsya Frida (JURNAL ILMIAH FEASIBLE: Bisnis, Kewirausahaan dan Koperasi, 2024)
Marketing research increasingly emphasizes the role of e-WOM in influencing consumer interest to buy products. Factors such as source credibility, number of reviews, platform type, and review content have been discussed in previous research on what influences e-WOM. This research is a descriptive qualitative research that uses literature studies as an approach. The results outline research from five journals that discuss e-WOM and how it affects consumer buying interest. These findings include the effect of the quality, quantity, and credibility of e-WOM on consumer buying interest. In the discussion, it was emphasized that consumer buying interest involves psychological, social, economic, and emotional components. E-WOM is also considered more trusting than official advertising because it utilizes aspects of identity and emotion, The result is that, by influencing the process of research, consideration, and consumer decisions, e-WOM has a positive impact on product buying interest by developing useful strategies to utilize it to achieve their business goals in the digital era.